1996
DOI: 10.1002/jlb.59.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Control of the production of soluble interleukin-4 receptors: implications in immunoregulation

Abstract: Soluble cytokine receptors (sCR) are generated in vivo through proteolytic cleavage of the membrane-bound receptors or by direct translation of mRNAs specifically encoding the soluble forms. Despite their widespread presence in biological fluids, the physiological role of endogenous sCR as immunoregulatory molecules is not yet well understood. In vivo, exogenous soluble interleukin-4 receptors (sIL-4R) have been shown to have both agonistic and antagonistic effects on IL-4 responses, depending on the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…First, the reduced neutralizing activity of the newly identified IL-4R allotype could be of importance in situations with a molar excess of the sIL-4R to the ligand (less efficient IL-4 antagonist). Second, during the early phase of a specific T cell response, when the concentrations of IL-4 exceed those of the sIL-4R, the sIL-4R may act as a transport molecule for IL-4 ( 47 ). The higher dissociation rate of the BALB/c sIL-4R allotype could result in a more rapid release of IL-4 in microenvironments with IL-4–responsive cells, prolonging the half-life of IL-4 (transporter function).…”
Section: Discussionmentioning
confidence: 99%
“…First, the reduced neutralizing activity of the newly identified IL-4R allotype could be of importance in situations with a molar excess of the sIL-4R to the ligand (less efficient IL-4 antagonist). Second, during the early phase of a specific T cell response, when the concentrations of IL-4 exceed those of the sIL-4R, the sIL-4R may act as a transport molecule for IL-4 ( 47 ). The higher dissociation rate of the BALB/c sIL-4R allotype could result in a more rapid release of IL-4 in microenvironments with IL-4–responsive cells, prolonging the half-life of IL-4 (transporter function).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation may be derived from a similar phenomenon that has been observed in the IL-4Rα system. In addition to being expressed on the cell surface, IL-4Rα is also expressed in a soluble form that stabilizes binding of IL-4 to membrane IL-4R complexes (IL-4Rα/γC) when IL-4 is in excess; however, when sIL-4Rα is in excess, sIL-4Rα sequesters IL-4 thus preventing activity [77]. Alternatively, the different activities of sIL-15Rα, agonist versus antagonist, may lie in the source of the protein.…”
Section: Prospective Alternatives To Trans-presentationmentioning
confidence: 99%
“…In vivo, exogenous sIL-4R has been shown to have both agonistic and antagonistic effects on IL-4 responses, depending on the relative concentration ratios of sIL-4R to IL-4. (66) Although competition with the membrane IL-4R is probably the basis for its inhibitory action, the mechanisms responsible for the potentiation of IL-4 activity are not completely clear but may involve alterations in the half-life and/or biodistribution of IL-4 in vivo. (67) We found that estrogen increases sIL-4R expression in OVX mice and propose that this might be a potential pathway for the preservation of the trabecular BMD.…”
Section: Sil-4r a Novel Estrogen-regulated Gene Of Potential Interesmentioning
confidence: 99%